Upper endoscopic findings in patients attending the endoscopy unit of al-azhar assiut university hospital: 2019–2020 - Hamdy M. Moustafa; Ahmed Q. Mohamed; Safwat S. Sawy; Amel A. Moustafa (Al-Azhar Assiut Medical Journal)
Background and aim An endoscope is a visual instrument used to inspect the internal cavities of the human body. Upper endoscopy has effective diagnostic and therapeutic functions; it can be used in patients with signs or symptoms suggestive of upper gastrointestinal (GI) disease, surveillance for upper gastrointestinal tract (GIT) malignancy in high-risk population, and also stoppage of upper GIT bleeding. The work is aimed to document the demographic characteristics, indications, endoscopic findings, and interventions done among patients referred to Al-Azhar Assiut University Hospital in the last 2 years (2019–2020). Patients and methods The study was conducted at the endoscopy unit in from January 2019 to December 2020. Results Our study showed that the most prevalent age group was aged between 20 and 50 years (65.4%). There is a slight predominance of female patients (51%) versus 49% who were males and the most common indications, while peptic ulcer disease was the most common endoscopic finding. Conclusion The most common indications were epigastric pain and upper GIT bleeding, while the most common GI finding was peptic ulcer disease. Also, esophageal varices were common esophageal findings for which band ligation and injection sclerotherapy were done.